Merangkul Diversitas Budaya melalui Matematika: Pendekatan Ethnomatematika dalam Pembelajaran Matematika di Sekolah - Madu, Aleksius (Jurnal Riset Pembelajaran Matematika, 2024)
This study is important to embrace cultural diversity in mathematics learning with the aim of implementing an ethnomathematics approach in mathematics learning to help embrace students' cultural diversity, improve mathematical understanding, and increase student motivation in learning mathematics. The writing method uses literature review. The literature review procedure starts by collecting data in the form of references related to the implementation of culture in mathematics learning with an emphasis on ethnomathematics in school mathematics learning, followed by analyzing these references and presenting the implications of the results of the literature review in learning activities. Analysis of the results contains a complete description of how to analyze the concept under study using an analytical approach, namely through the process of analyzing data or information by providing arguments through logical thinking and then a conclusion is drawn. The implementation of Ethnomathematics in education is an important step towards a more inclusive, relevant and culturally oriented education. It helps to embrace the cultural diversity of students, improve mathematical understanding, and increase student motivation.